PENGARUH LEVEL INTERPHASE TERHADAP NILAI SPLITTING DEGREE DAN YIELD PRODUKSI PADA PROSES HIDROLISIS PADA COLUMN SPLITTING - Ramadhan, Aldi Dwi; Luthfi, Muhammad Zulfikar (Politeknik ATI Padang, 2020)
A company in North Sumatra is engaged in the processing of palm oil into fatty acid and glycerin. In the current industrial process, crude palm oil is hydrolyzed into fatty acids and glycerol at a temperature of 250°C and a pressure of 53 bar for 7-8 hours in a splitting column. The success rate of the hydrolysis reaction is measured by the splitting degree, where a higher splitting degree indicates a more complete hydrolysis reaction. A common issue is that the acid value and saponification value in the splitting process are not optimal due to factors such as the height of the interphase level. The acid value and saponification value are crucial in determining the splitting degree. Therefore, it is necessary to analyze the impact of the interphase level on the splitting degree and the yield of the hydrolysis process in the splitting column. The results indicate that the efficient interphase level for the fat splitting hydrolysis process is at 3 oil = 4.2 meters (Point 0).